ABO Blood Group as a Model for Platelet Glycan Modification in Arterial Thrombosis. Issue 7 (July 2015) - Zhong, Ming; Zhang, Hanrui; Reilly, John P.; Chrisitie, Jason D.; Ishihara, Mayumi; Kumagai, Tadahiro; Azadi, Parastoo; Reilly, Muredach P.
Abstract : ABO blood groups have long been associated with cardiovascular disease, thrombosis, and acute coronary syndromes. Many studies over the years have shown type O blood group to be associated with lower risk of cardiovascular disease than non–type O blood groups. However, the mechanisms underlying this association remain unclear. Although ABO blood group is associated with variations in concentrations of circulating von Willebrand Factor and other endothelial cell adhesion molecules, ABO antigens are also present on several platelet surface glycoproteins and glycosphingolipids. As we highlight in this platelet-centric review, these glycomic modifications may affect platelet function in arterial thrombosis. More broadly, improving our understanding of the role of platelet glycan modifications in acute coronary syndromes may inform future diagnostics and therapeutics for cardiovascular diseases.